Long-term burden of war injuries among civilians in LMICs: case of the July 2006 war in Lebanon - Kobeissi, Elsa; Menassa, Marilyne; Honein-AbouHaidar, Gladys; El Achi, Nassim; Abdul-Sater, Zahi; Farhat, Theresa; Al Mohtar, Dalia; Hajjar, Marwan; Abdul-Khalek, Rima A.; Chaya, Bachar F.; Elamine, Ahmad; Hettiaratchy, Shehan; et al. (Frontiers in Public Health, 2023)
Lebanon, a country located on the eastern shore of the Mediterranean Sea, is one of the world's smaller sovereign states. In the past few decades, Lebanon endured a perpetual political turmoil and several armed conflicts. July 12, 2006, marked the start of a one-month war in Lebanon, which resulted in thousands of casualties. Little is known about the long-term consequences of war injuries inflicted on civilians during the July 2006 war. The objectives of this paper were to identify and evaluate: 1-civilians' access to healthcare and medicine under conditions of war; 2the long-term socioeconomic burden on injured civilians; and 3-their quality of life more than a decade post-war. We adopted a mixed-method research design with an emphasis on the qualitative component. We conducted interviews with patients, collected clinical and financial data from hospital medical records, and administered a self-rated health questionnaire, the EQ-5D-5L. Simple descriptive 2 statistics were calculated using Excel. NVivo 12® was used for data management and thematic analysis.We conducted 25 interviews. Injured civilians were mostly males, average age of 27. The most common mechanism of injury was blast injury. Most patients underwent multiple surgeries as well as revision surgeries. The thematic analysis revealed three themes: 1-recall of the time of the incident, the thousand miles journey, and patients' access to services; 2post-trauma sequelae and services; and 3-long-term impact. Patients described the long-term burden including chronic pain, poor mobility, anxiety or depression, and limited activities of daily living.Civilians injured during the July 2006 war described the traumatising events they endured during the war and the limited access to medical care during and post-war. Up until this study was conducted, affected civilians were still experiencing physical, psychological, and financial sequelae. Acknowledging the limitations of this study, which include a small sample size and recall bias, the findings underscore the necessity for the expansion of services catering to civilians injured during wartime.Thus, more services need to be offered to civilians injured during war.